Initial In-Brace Correction: Can the Evaluation of Cobb Angle Be the Only Parameter Predictive of the Outcome of Brace Treatment in Patients with Adolescent Idiopathic Scoliosis? - Angelo Gabriele Aulisa; Marco Galli; Marco Giordano; Francesco Falciglia; Silvia Careri; Renato Maria Toniolo (MDPI AG, 2022)
Background: Patients with a better initial in-brace correction could show a higher probability of a successful outcome. However, no one has investigated whether parameters can affect the outcomes. The aim of this retrospective study was to evaluate if the initial correction rate (ICR) could be predictive of the bracing outcome and to determine the role of some mechanical and biological parameters in ICR. Methods: The study population comprised 449 patients who met the inclusion criteria. Curve correction > 10° Cobb defines brace treatment success. Success and failure groups were compared in terms of the Risser sign, initial Cobb angle, initial Perdriolle value and ICR. Results: ICR significantly correlates with initial Perdriolle. The success group had a significantly lower value of Pedriolle and initial Cobb angles, Risser sign and ICR than the failure group. The ICR and lower Risser were significantly associated with the brace treatment outcome. This seems particularly suitable for positivity prediction (Predicting value VP+: 87%). Conclusions: This study confirms that immediate in-brace correction can foretell the brace treatment outcome. Patients with a low Risser sign and a high rate of in-brace correction showed a bracing success of 87%. A correlation between rotation and in-brace correction confirms that rotation is among the parameters that influence the deformed spine reaction to corrective actions the most.